Social dimension of food poverty of female-headed households after Covid-19 and economic crisis in Sri Lanka - Mohamed Yaseen Minnathul Suheera; Thaseem Mohamed Fathima Wazeema (SIMULACRA: JURNAL SOSIOLOGI, 2023)
The economic crisis in early 2022 in Sri Lanka has had a massive negative impact on the social and economic life of female-headed households in the country. In particular, food poverty affects many families. This study was conducted to investigate the food consumption patterns of female-headed households after the economic crisis in Sri Lanka. Female headed households in five Divisional Secretariat Division of Ampara District were selected as the study sample based on purposive sampling techniques. Qualitative research methodology was used. In-depth interview and focused group discussion were used as primary data collection tools. The collected data were analyzed using thematic analysis method. The study found that after the economic crisis in Sri Lanka, there was a massive decline in food consumption, quality of food consumed and quantity of food consumed by female-headed households. Most female-headed households consume food only to satisfy hunger. Very small households have maintained the quality of food consumption, which has put them in debt. Traditional food consumption practices have changed and new food habits have emerged in certain families. The study suggests that the prevalence of food poverty among female-headed households should be addressed immediately and alternative programs should be designed to improve their condition.